2009
DOI: 10.1002/masy.200950931
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Chain Collapse in Supercritical Fluids. 1. Molecular Simulation Results

Abstract: A few years ago we reported the first observation, by computer simulations, of polymer chain collapse near the lower critical solution temperature (LCST).1 In the present work, we extended the above study to understand the underlying physics of a single polymer chain collapse near LCST and its relationship to phase boundaries in the T‐x plane. Effects of solvent and monomer sizes, and solvent and monomer energetic interactions are studied. Using Monte Carlo simulations, the mean end‐to‐end distance (R) and gyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 49 publications
9
11
0
Order By: Relevance
“…For this case, the CGT is predicted to drop monotonically with increasing solvent density, as depicted by the solid line in Figure , based on eq . This result is consistent with simulations of Lennard-Jones polymer chains, which exhibit an approximately linear reduction in Θ̃ with density up to dimensionless densities around 0.6. , …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…For this case, the CGT is predicted to drop monotonically with increasing solvent density, as depicted by the solid line in Figure , based on eq . This result is consistent with simulations of Lennard-Jones polymer chains, which exhibit an approximately linear reduction in Θ̃ with density up to dimensionless densities around 0.6. , …”
Section: Resultssupporting
confidence: 90%
“…Historically, much of the theoretical attention in this area has focused on the relatively low temperature cooling-induced coil-to-globule transition that is associated with the upper critical solution temperature (UCST) phase boundary predicted by the Flory–Huggins solution theory. , More recently, it has become clear that a heating-induced chain collapse, found at higher temperatures and associated with the lower critical solution temperature (LCST) phase boundary, is central to diverse applications of synthetic polymers and the functionality of many biopolymers. This transition is of particular interest in the development of stimuli responsive polymers (such as poly­( N -isopropylacrylamide) and the understanding of conformational behavior in DNA and proteins. Chain conformational behavior at high temperatures and/or low solvent densities more broadly is also relevant to new polymer processing techniques: it impacts the processing of polymers in supercritical solvents , and has been implicated in determining the properties of ultrastable polymer glasses produced via matrix-assisted pulsed laser evaporation . Despite this situation, the LCST-related CGT and high-temperature conformational behavior more generally have received relatively little theoretical attention compared to conformational behavior at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…We begin by considering the glass formation behavior of these individual polymer chains in a vacuum. In the temperature range relevant to glass formation, these chains assume a collapsed globular state, shown in Figure , consistent with the understanding that polymer chains in a vacuum or gas assume a collapsed globular state rather than an ideal random walk. While we have not observed a transition to an expanded coil state in these simulations, it is evidently above the maximal temperature of 1.5 probed in these simulations, with prior simulation and theory work suggesting that it lies in the temperature range of 2 to 3. 256-bead and 1000-bead chain globules exhibit mean surface radii of ≈4σ and ≈6σ, respectively, near T g , corresponding to ≈4 or ≈6 nm. The glass transition of a polymer surrounded by a soft liquid medium is similar to the same material surrounded by a gas or vacuum, making this a reasonable model for glass formation of a globular macromolecule in solution.…”
Section: Resultssupporting
confidence: 83%
“…The results presented here are in agreement with the previous work of Luna-Barcenas et al who carried out an extensive simulation study of an n = 20 LJ polymer in supercritical LJ solvent. 17,18,38,39 These authors have drawn connections between the single chain in solvent and the behavior of a polymer solution. They show that the LJ chainin-solvent system displays both upper and lower solution critical behaviors and an associated closed-loop immiscibility curve.…”
Section: Discussionmentioning
confidence: 99%
“…We present results for chains up to length n = 800 and are able to make direct comparison with full chain in explicit solvent simulations for chains up to length n = 100. The LJ chain-in-solvent system has been the subject of a detailed study by Luna-Barcenas et al 17,18,38,39 who have shown that this system contains both an upper and lower solution critical point suggesting a closed loop immiscibility curve in dilute solutions. The LJ system also allows us to explore chain structure in the neighborhood of a solvent critical point.…”
Section: Introductionmentioning
confidence: 99%